Thermal radiation effects on hydromagnetic flow - Abdelkhalek, Mohamed M. (Computer Assisted Methods in Engineering and Science, 2007)
Numerical results are presented for the effects of thermal radiation, buoyancy and heat generation or absorption on hydromagnetic flow over an accelerating permeable surface. These results are obtained by solving the coupled nonlinear partial differential equations describing the conservation of mass, momentum and energy by a perturbation technique. This qualitatively agrees with the expectations, since the magnetic field exerts a retarding force on the free convection flow. A parametric study is performed to illustrate the influence of the radiation parameter, magnetic parameter, Prandtl number, Grashof number and Schmidt number on the profiles of the velocity components and temperature. The effects of the different parameters on the velocity and temperature profiles as well as the skin friction and wall heat transfer are presented graphically. Favorable comparisons with previously published work confirm the correctness of numerical results.